Ethical Approval in Nepal: Barriers or Facilitators? - Ghimire, Namita; Pandey, Sony; Joshi, Pramod; Adhikari, Ramesh Kant (Journal of Nepal Health Research Council, 2024)
Any research involving human participants requires review and approval from an authorized research ethics committee to safeguard participant's rights, dignity and welfare while ensuring the scientific validity of the research. Ethical approval is mandatory before initiating or ecruiting study participants. It is also a prerequisite for publishing research findings in scientific journals contributing to ensuring the quality of scientific knowledge. The ethical review process focuses on the assessment of potential risks to the participants as well as the research team focusing on how such risks are identified, minimized and managed. This paper provides an overview of the Nepal Health Research Council's ethical review and approval process for both national and international researchers intending to conduct health research in Nepal. Despite this, the Nepalese ethics committee and researcher face several challenges, including limited awareness of responsible conduct of research, limited training opportunities, unclear clinical trial guidelines, bureaucratic hurdles, and frequent staff turnover in research governance. This paper highlights these challenges and aims to support both researchers and the Ethics Committee in promoting the responsible conduct of health research in Nepal. Keywords: Ethical issues; ethical review and approval; Nepal and research.